Adsorption and desorption behavior of arsenite and arsenate at river sediment-water interface. (1st September 2022) - Nguyen, Kien Thanh; Navidpour, Amir Hossein; Ahmed, Mohammad Boshir; Mojiri, Amin; Huang, Yuhan; Zhou, John L.
Abstract: The adsorption of inorganic arsenic (As) plays an important role in the mobility and transport of As in the river environment. In this work, the adsorption and desorption of arsenite [As(III)] and arsenate [As(V)] on river sediment were conducted under different pH, initial As concentrations, river water and sediment composition to assess As adsorption behavior and mechanism. Both adsorption kinetics and equilibrium results showed higher adsorption capacity of sediment for As(V) than As(III). Adsorption of As(III) and As(V) on river sediment was favored in acidic to neutral conditions and on finer sediment particles, while sediment organic matter marginally reduced adsorption capacity. In addition, higher adsorption affinity of As(III) and As(V) in river sediment was observed in deionised water than in river water. For the release process, the desorption of both As(III) and As(V) followed nonlinear kinetic models well, showing higher amount of As(III) release from sediment than As(V). Adsorption isotherm was well described by both Langmuir and Freundlich models, demonstrating higher maximum adsorption capacity of As(V) at 298.7 mg/kg than As(III) at 263.3 mg/kg in deionised water, and higher maximum adsorption capacity of As(III) of 234.3 mg/kg than As(V) of 206.2 mg/kg in river water. The XRD showed the changes in the peaks of mineral groups of sediment whilst FTIR results revealed the changes related to surface functional groups before and after adsorption, indicating that Fe–O/Fe–OH, Si(Al)–O, hydroxyl and carboxyl functional groups were predominantly involved in As(III) and As(V) adsorption on sediment surface. XPS analysis evidenced the transformation between these As species in river sediment after adsorption, whilst SEM-EDS revealed higher amount of As(V) in river sediment than As(III) due to the lower signal of Al. Graphical abstract: Image 1 Highlights: Sediment surface functional groups were involved in As adsorption. There was transformation between As species on sediment. Adsorption kinetics followed the pseudo first- and second-order models. Adsorption equilibria were well fitted by the Langmuir and Freundlich isotherms. Fine sediment fractions significantly enhanced As(III) and As(V) adsorption.